The bothersomeness of sciatica: patients’ self-report of paresthesia, weakness and leg pain - Grøvle, Lars (Springer-Verlag, 2009)
The objective of the study was to investigate how patients with sciatica due to disc herniation rate the bothersomeness of paresthesia and weakness as compared to leg pain, and how these symptoms are associated with socio-demographic and clinical characteristics. A cross-sectional study was conducted on 411 patients with clinical signs of radiculopathy. Items from the Sciatica Bothersomeness Index (0 = none to 6 = extremely) were used to establish values for paresthesia, weakness and leg pain. Associations with socio-demographic and clinical variables were analyzed by multiple linear regression. Mean scores (SD) were 4.5 (1.5) for leg pain, 3.4 (1.8) for paresthesia and 2.6 (2.0) for weakness. Women reported higher levels of bothersomeness for all three symptoms with mean scores approximately 10% higher than men. In the multivariate models, more severe symptoms were associated with lower physical function and higher emotional distress. Muscular paresis explained 19% of the variability in self-reported weakness, sensory findings explained 10% of the variability in paresthesia, and straight leg raising test explained 9% of the variability in leg pain. In addition to leg pain, paresthesia and weakness should be assessed when measuring symptom severity in sciatica.